Adult Ectopic Cervical Thymic Tissue in relation to a Parathyroid Adenoma and a Papillary Thyroid Carcinoma: A Report of Two Cases - Vijay Shrawan Nijhawan; Roopali Sehrawat; Neeti Goyal; Manish Gupta (Case Reports in Otolaryngology)
Ectopic cervical thymus is a rare congenital anomaly, which results because of the failure of complete descent of the thymus. They are incidental findings in the young and may disappear during the early years of life; however, they have rarely been described in adults. Some of them may undergo hyperplasia or neoplastic transformation and become visible or cause symptoms. We report two rare cases of incidentally detected cervical thymic tissue in adults. In one case, the thymic tissue was seen adjacent to a parathyroid adenoma of the left inferior parathyroid gland. In the other, it was seen adjacent to the left inferior parathyroid gland in a case of papillary thyroid carcinoma. In both these cases, the ectopic thymic tissue was diagnosed as a result of pathological examination, not clinically by macroscopic appearance during operation or radiological evaluation. The finding needs to be noted as these ectopic foci can occasionally give rise to hyperplasia and neoplasms of the thymus.